A Clown’s True Colors in Thomas Mann’s Short Story „Mario and the Magican” and Heinrich Böll’s Novel „The Clown” - Głuszko-Boczoń, Estera (Not just the Clown and the Tiger. Sketches about Circus Arts, 2019)
The aim of this paper is to present a different, unknown side of the clown’s personality. At first sight the character of the clown seems to be unambiguous. He is supposed to entertain the audience, make people laugh and be funny. The clown is not expected to reflect or have wisdom… Therefore, the clown characters presented in T. Mann’s short story Mario and the Magician and in H. Böll’s novel The Clown seem to be even more interesting. They go far beyond their expected roles, break stereotypes, bring reflection and show the true side of their personality which often turns out to be surprising or even dangerous.